2006
DOI: 10.1007/s00264-006-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of long-term results following high tibial osteotomy in patients under 60 years of age

Abstract: We have investigated, in a prospective study, the outcome of a valgus osteotomy of the tibia in patients less than 60 years of age with arthrosis of the medial compartment and a varus angle of no more than 177.7°. Included in the study were 44 high tibial osteotomies (HTO) performed in 42 patients from 1981 until 1996. There were 35 females (2 bilateral) and 7 males, with an average age of 51 years (range: 30-60 years). Only patients in the first three grades, according to Ahlback's classification, were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 22 publications
4
51
1
1
Order By: Relevance
“…Papachristou et al [34] followed up 44 closing wedge HTO, fixed with one or two staples. Survivorship analysis showed a success rate of 80% at ten years, 66% at 15 years and 53% at 17 years from surgery.…”
Section: Overall Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papachristou et al [34] followed up 44 closing wedge HTO, fixed with one or two staples. Survivorship analysis showed a success rate of 80% at ten years, 66% at 15 years and 53% at 17 years from surgery.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Zhim et al [45] compared the biomechanical stability of the Puddu plate (Arthrex, Naples, FL, USA) and the Hoffman II external fixator (Stryker Howmedica, Osteonics, Ruther- Naudie et al [33] 1999 75% at 5 years, 51% at 10 years, 39% at 15 years and 30% at 20 years Sprenger and Doerzbacher [39] 2003 65-74% at 10 years Koshino et al [30] 2004 97.3% at 7 years, 95.1% at 10 years and 86.9% at 15 years Tang and Henderson [43] 2005 89.5% at 5 years, 74.7% at 10 years and 66.9% at 15 and 20 years Papachristou et al [34] 2006 80% at 10 years, 66% at 15 years and over 52.8% at 17 years of follow-up Flecher et al [22] 2006 85% at 20 years Gstöttner et al [24] 2008 94% at 5 years, 79.9% at 10 years, 65.5% at 15 years and 54.1% at 18 years Akizuki et al [3] 2008 97.6% at 10 years and 90.4% at 15 years ford, NJ, USA) and concluded that plate fixation was superior in maintaining correction. Spahn et al [38] in their biomechanical investigation on four different fixation devices (conventional plate, angle stable plate with or without spacer), concluded that spacer implants have superior properties and that angle stable plates may prevent fractures of the lateral cortex.…”
Section: Type Of Fixationmentioning
confidence: 99%
“…Nowadays, it remains a good option [2,3,6,9,10,13,16,17,22], despite the large increase in total knee replacement (TKR) or the revival of unicompartmental knee prosthesis boosted by the lessinvasive surgery concept. It is best indicated for "young" and active people (less than 65 years of age) with moderate arthritis (narrowing joint line up to 100% without any bone wear or instability).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Papachristou et al (2), it was specified that the results obtained were excellent in 61.3% of patients, good in 20.4%, moderate in 6.8%, and poor in 6.8% of patients. Efe et al (13) reported the outcome of surgery to be excellent in 54 patients, good in 74 patients, moderate in 51 patients, and poor in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generally included radiological evaluations and assessed the need for arthroplasty. However, the thoughts about the operation that patients underwent and sometimes the outcome of the operation have been ignored (1)(2)(3)(4)(5)(6)(7)(8). In this study, mid-phase results of successive 99 HTO operations performed with the proper indication and technique in our hospital were examined, considering the patients' thoughts about the surgery and the outcomes of the operations.…”
Section: Introductionmentioning
confidence: 99%